The Correlation between Premenopausal Estrogen and Estrogen Receptors in Breast Cancer - Kurnia, Ahmad; Pratama, Dedy; Mirwan, Muhammad (The New Ropanasuri Journal of Surgery, 2022)
Introduction. The correlation between the premenopausal estrogen hormone and estrogen receptors is unknown. The hormone estrogen has a risk factor for causing breast cancer. Meanwhile, the estrogen receptor plays a role in determining further treatment plans in breast cancer patients. Patients with high estrogen receptors have a better prognosis. If the premenopausal estrogen hormone can affect the estrogen-receptor, then the estrogen hormone can be modified to have a better prognosis. Method. A cross-sectional study enrolled 32 subjects with complete data and was statistically analyzed to find the correlation between premenopausal estrogen hormone and estrogen-receptors. Results. The estradiol ranged from 15.3 − 89.8 pg/mL, and estrogen receptors showed a range of 10–90%. The Spearman correlation test between the estradiol and the estrogen receptor showed a p-value = 0.864 and a negative correlation coefficient of 0.032. Conclusion. Estrogen hormone is not statistically associated with estrogen receptors in premenopausal breast cancer patients, thus illustrating that the prognosis of breast cancer is not associated with the estrogen hormone